Leadership experiences, labor market entry, and early career trajectories - Martin Lundin; Oskar Nordström Skans; Pär Zetterberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
We study how leadership experiences before labor market entry affect subsequent labor market performance, using a regression discontinuity design to isolate the causal effects. The design is applied to elections of representatives at Swedish student union (SU) councils. Archive data on winning and losing candidates at three major Swedish universities are mapped to register data on their subsequent labor market careers. The results show that students who acquired a position in the SU councils are more likely to have a rapid transition into employment than candidates who just missed getting to get such a leadership role. The employment effects are not confined to workplaces, organizations, or industries where previous candidates are employed, suggesting that the benefits of having been a student representative are general in nature. Elected representatives are more likely to hold a well-paid job within three years, but not thereafter. Overall, our estimates suggest that leadership experiences before labor market entry boost individuals' initial career trajectories, whereas mid-term outcomes appear unaffected.
Keywords: I26; I23; J24; 330; leadership experiences; extracurricular activities; labor market entry; earnings; higher education; non-cognitive skills